PENYIMPANGAN PERILAKU SEKSUAL TERHADAP TINDAK PIDANA MUTILASI; SUATU TINJAUAN PSIKOLOGI KRIMINAL - Siregar, Lis Yulianti (IAIN Padangsidimpuan, 2020)
Criminal psychology is the science of psychology (behavioral and psychiatric conditions) villains and all related directly or indirectly to the acts committed and the consequences. Criminal psychology in this case also studied the behavior of individuals in particular and why it appears social behavior or criminal nature. According to psychologists, the crime is a human behavior that is unlawful.